2014
DOI: 10.1007/s11743-014-1658-2
|View full text |Cite
|
Sign up to set email alerts
|

Fabric Softener Technology: A Review

Abstract: This paper reviews current and emerging fabric softener technologies including various benefits that can be achieved by manipulating quat active structure, polymer/ quat active combination systems, single rinse products, consumer product forms, softening-through-the-wash, and fragrances used in fabric softeners. The technologies reviewed are aimed at the consumer market. Insights are provided into the drivers behind the technologies as well as their influence on market trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 7 publications
0
46
0
2
Order By: Relevance
“…Although softeners were used for decades [3], there is still a lack of consensus pertaining to the active deposition on cotton fibers as well as on the softening mechanism. It has been shown that the surfactants used in conditioners are self-assembled into micron size vesicles [4][5][6].…”
mentioning
confidence: 99%
“…Although softeners were used for decades [3], there is still a lack of consensus pertaining to the active deposition on cotton fibers as well as on the softening mechanism. It has been shown that the surfactants used in conditioners are self-assembled into micron size vesicles [4][5][6].…”
mentioning
confidence: 99%
“…In addition, a review of the literature data (Calero et al, ; Lai, ; Murphy, ; Ogorzałek et al, ; Smulders, ; Wasilewski et al, ; Zoller, ) and the results of viscosity measurements performed for the commercial formulations presented in an article by the main author (Ogorzałek, Ogorzalek, ) indicated that the viscosity of this type of formulations ranged from ca. 20 to ca.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a review of the literature data (Calero et al, 2010;Lai, 2006;Murphy, 2015;Ogorzałek et al, 2019;Fig. 2 Particle size distribution in 1% aqueous solutions of the transparent fabric softeners without added extract and with 0.3% of raspberry seed extracts Smulders, 2002;Wasilewski et al, 2016a;Zoller, 2008) and the results of viscosity measurements performed for the commercial formulations presented in an article by the main author (Ogorzałek, Ogorzalek, 2017) indicated that the viscosity of this type of formulations ranged from ca.…”
Section: Effect Of Hydrophobic Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fabric softeners are expected to be easily dispersible in water and should not cause fabric yellowing and corrosion of structural elements in washing machines. [1][2][3][4][5][6][7][8][9] The functions of fabric softeners determine their names. The products are also referred to as anti-static agents or fabric softeners.…”
Section: Introductionmentioning
confidence: 99%